Erotismo en la poesía Nauatl. "Canto a las mujeres de Chalco" - Arley, Mauricio (2013)
This analysis will show how the erotic practice is built in a nahuatl poem. The erotism is an art that comes from an active woman. The main metaphor consists in knowing that wars between countries generate conquers, but it also occurs in the love field, where the women domain.